2003
DOI: 10.1089/107632703764664792
|View full text |Cite
|
Sign up to set email alerts
|

Viable Osteogenic Cells Are Obligatory for Tissue-Engineered Ectopic Bone Formation in Goats

Abstract: In this study we investigated the bone-forming capacity of tissue-engineered (TE) constructs implanted ectopically in goats. As cell survival is questionable in large animal models, we investigated the significance of vitality, and thus whether living cells instead of only the potentially osteoinductive extracellular matrix are required to achieve bone formation. Vital TE constructs of porous hydroxyapatite (HA) covered with differentiated bone marrow stromal cells (BMSCs) within an extracellular matrix (ECM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(150 citation statements)
references
References 48 publications
5
143
0
2
Order By: Relevance
“…42 It could be demonstrated that allogenic green fluorescence-labeled BMCC survive for approximately 11 weeks in mice, but the amount of new bone formation synthesized by these cells was very limited. 36,37 Transplanted cells usually face a hostile immune system, they lack grown physiological connections with the host tissues, and the supply with nutrition and other factors is problematic. Moreover, the transplanted cells compete directly with mumerous host cell types that are recruited from the organism for the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…42 It could be demonstrated that allogenic green fluorescence-labeled BMCC survive for approximately 11 weeks in mice, but the amount of new bone formation synthesized by these cells was very limited. 36,37 Transplanted cells usually face a hostile immune system, they lack grown physiological connections with the host tissues, and the supply with nutrition and other factors is problematic. Moreover, the transplanted cells compete directly with mumerous host cell types that are recruited from the organism for the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Twelve weeks after the implantations, each animal was sacrificed by an overdose of pentobarbital (Euthesaat, Organon, Oss, The Netherlands) and potassium chloride.…”
Section: Animals and Implantationmentioning
confidence: 99%
“…To regenerate bone tissue in vivo, viable MSCs are required, but whether they directly differentiate or retain proliferative capacity is unclear. 17 We applied BLI to an ectopic implantation model to investigate the fate of MSCs in vivo. BLI has proven to be a powerful technology for noninvasive imaging in animal models of oncological diseases and in bone tissue engineering studies 18 and is often used to measure cell proliferation on the basis of luciferase gene expression.…”
Section: Discussionmentioning
confidence: 99%